ANALISIS EFEKTIVITAS METODE FLIPPED CLASSROOM DENGAN MEDIA EDPUZZLE TERHADAP PEMBELAJARAN TEKS PUISI DI SMPN 9 PRABUMULIH - Santy Anggraini, Dwi; Wardiah, Dessy; Wahidy, Ahcmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the flipped classroom method supported by Edpuzzle media in improving students' learning outcomes in poetry text material. The research was motivated by the low understanding of poetry among eighth-grade students at SMPN 9 Prabumulih, who considered the material abstract and less relevant to daily life. The research employed a quasi-experimental design with a pretest-posttest control group design. The sample consisted of two classes selected by cluster random sampling, with class VIII.1 as the experimental group and VIII.2 as the control group, each comprising 28 students. Data were collected through tests, observations, and documentation. The results showed that the experimental class experienced a significant increase in learning outcomes compared to the control class. The use of Edpuzzle in the flipped classroom model allowed students to learn the basic material independently before class and engage in interactive discussions during classroom sessions. Hypothesis testing using a paired sample t-test revealed a significant difference in learning outcomes between the two groups. This indicates that the flipped classroom method supported by Edpuzzle media is effective in enhancing students' understanding of poetry texts and can serve as an alternative to conventional teaching methods.